AB0093 Efficacy of Radiation Synovectomy (Radiosynovectomy or Radiosynoviorthesis) with Yttrium-90 (Y-90) in Exudative Inflammation of Synovial Membrane of Knee Joints in Patients with Rheumatic Diseases. (9th June 2015) - Zalewska, J.; Dankiewicz-Fares, I.; Wojciechowski, R.; Jeka, S.
Abstract : Background: Hypertrophic and exudative synovitis of knee is one of the earliest symptoms in rheumatic diseases. In case of pharmacotherapy failure, other methods which directly remove the inflamed synovial membrane- synovectomies are used. Radiosynovectomy (RSV) is a radiopharmaceutical admission of colloidal solution to cavity joints. Objectives: In this publication, the authors decided to assess the efficacy of knee RSV with Yttrium-90 (Y-90) in several groups of patients with rheumatic diseases.We have also proposed the algorithm for patients with recurrent knee effusion. Methods: The study group was 100 patients in age from 20 to 82 years with hypertrophic-exudative synovitis of knee in rheumatic diseases (47 patients with RA, 33 patients with OA, 10 patients with psoriatic arthritis and 10 patients with AS). Radiopharmaceutical colloid of Y-90, with radiation dose 185-222 MBq in a volume of 2-3 ml, was administered to joint. The knee was immobilized for 72 h. The effect of treatment was monitored by the use of objective methods: evaluation of acute phase indicators- ESR and CRP, ultrasound- evaluation of synovial hypertrophy, joint effusion quantity and synovial vascularisation in power color Doppler and subjective methods, which include the assessment of patient questionnaires (HAQ, SF-36, FACIT, EQ- 5D, WOMAC), VAS-Visual Analogue Scale pain intensity by patient and the VAS-Visual Analogue Scale disease activity by patient and physician. The visits were performed at 1, 3 and 6 months after RSV. Results: In all groups of patients, we have noticed a statistically significant change concerning the reduction of synovial hypertrophy, the quantity of synovial fluid and synovial membrane activity in power color Doppler option decrease assessed in ultrasound examination. We have observed the best treatment efficacy in patients with RA.We have also noticed significant improvement in the assessment of health status in the whole group of patients, according the questionnaires: HAQ, SF-36, EQ-5D and FACIT, VAS pain assessed by patient and VAS disease activity assessed by patient and physician. Conclusions: RSV is an effective and safe method of treatment hypertrophic-exudative synovitis of knee, which is resistant to use of pharmacological drugs and intraarticular glucocorticosteroids injections. In therapeutic algorithm RSV should be located between conservative treatment and operative procedures. RSV does not require hospitalization and prolonged rehabilitation. Disclosure of Interest: None declared